Instrumen Pengetahuan Seksualitas untuk Anak - Nirmala, Ine; Feronica, Feronica Eka (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2017)
The cultivation of knowledge and understanding of sex education in early childhood is very important at the present time. From the results of initial observation found that there is a discrepancy between the content standards, process standards and evaluation / rating standards, which will result in the gap in the assessment results of each school, especially in sexual knowledge, namely in the understanding of gender, male gender differences and women, self-protection from sexual violence, self-concept. After going through several stages of the study produced a final product of the instrument of sexual knowledge of children aged 5-6 years are made as a module of teachers in assessing sexual preoccupation of children aged 5-6 years in the realm of Early Childhood Education. The instrument has met the good test criteria in accordance with the analysis of the problems that have been done. The product is in the form of a guidance guide module for teachers which contains 16 guided questions, in each question along with a behavioral and behavioral assessment guide in the childs sexual knowledge field that is consistent with an indicator of sexual knowledge of children aged 5-6 years.